Incidencia del clima laboral en la calidad de atención al usuario en la fundación Dr. Oswaldo Loor del cantón Portoviejo - Loor Lucas, María Dayana (2022)
The purpose of this research was to determine the impact of the work environment on the quality of user service at the Dr. Oswaldo Loor Foundation in the Portoviejo canton. For its development, a sample of 150 users and 47 collaborators of the foundation was used. bibliographical information consulted in different sources such as theses, books and scientific articles, which gives it an academic weight, also, it had field research that allowed reaching the scene, in addition to complementing the investigative process, the methods were used descriptive, deductive, inductive and correlational, which together allowed to explain the most relevant findings, these results are comprised of three phases that correspond to the specific objectives of the research, techniques such as the survey that was applied to the sample were used in them chosen, the interview that was applied to the manager of the institution, and statistical techniques that They allowed to graph and correlate the data obtained in the applied instruments, additionally, to obtain effective results, tools such as the questionnaire, interview guide, and SPSS were used, thus reflecting that in the entity there is a gap between the relevant percentage and communication variables, motivation and response capacity, which reflected a lower average, therefore, a 5W+1H matrix was executed in order to establish an improvement plan that contributes to the strengthening of the relevant activities and direct the work in the institution to improve the conditions of the working environment and the quality of customer service.